2005
DOI: 10.1128/mcb.25.2.612-620.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Parafibromin Tumor Suppressor Protein Is Part of a Human Paf1 Complex

Abstract: Parafibromin, the product of the HRPT2 (hyperparathyroidism-jaw tumor syndrome 2) tumor suppressor gene, is the human homologue of yeast Cdc73, part of the yeast RNA polymerase II/Paf1 complex known to be important for histone modification and connections to posttranscriptional events. By purifying cellular parafibromin and characterizing its associated proteins, we have identified a human counterpart to the yeast Paf1 complex including homologs of Leo1, Paf1, and Ctr9. Like the yeast complex, the parafibromin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
242
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(267 citation statements)
references
References 34 publications
22
242
2
1
Order By: Relevance
“…The nuclear localization of parafibromin is in agreement with the results of three other studies (Tan et al, 2004;Hahn and Marsh, 2005;Rozenblatt-Rosen et al, 2005). Parafibromin is a 61 kDa protein, and it has been reported that proteins with a molecular mass >45 kDa cannot diffuse freely across the nuclear envelope and require to be actively transported through the nuclear pore complex via a process that involves recognition by the importins of NLSs in the proteins (Quadrini and Bieker, 2002;Vandenbroucke et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The nuclear localization of parafibromin is in agreement with the results of three other studies (Tan et al, 2004;Hahn and Marsh, 2005;Rozenblatt-Rosen et al, 2005). Parafibromin is a 61 kDa protein, and it has been reported that proteins with a molecular mass >45 kDa cannot diffuse freely across the nuclear envelope and require to be actively transported through the nuclear pore complex via a process that involves recognition by the importins of NLSs in the proteins (Quadrini and Bieker, 2002;Vandenbroucke et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, transient over-expression of parafibromin inhibits cyclin D1 expression whereas downregulation of parafibromin using small interfering RNA (siRNA) leads to premature entry of cells into S phase (Woodard et al, 2004;Yart et al, 2005). In addition, parafibromin is associated with a Set-1-like histone methyltransferase (HMTase) complex that methylates H3 on lysine 4, and thereby initiates transcription by chromatin modification and activation of RNA polymerase II (Rozenblatt-Rosen et al, 2005;Yart et al, 2005). Interestingly, the tumour suppressor menin has also been shown to be associated with a Set-1-like HMTase complex and RNA polymerase II, although it is important to note that menin and parafibromin have not been shown to have a direct interaction (RozenblattRosen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of such a view, both mutant species display proper nuclear localization and retain their ability to bind to components of the Paf1 complex including Paf1, Leo1 as well as URI (this report; Rozenblatt-Rosen et al, 2005;Yart et al, 2005). Thus, it is possible that Paf1 complexes formed with either the K34Q or L64P mutant are defective in one or more aspects of the gene expression pathway.…”
Section: Discussionmentioning
confidence: 66%
“…The two mutations gave rise to K34Q and R292K amino-acid change in parafibromin's primary sequence. With the exception of another missense mutation (L64P), all the described mutations arising in the HRPT2 gene cause C-terminal truncated variants of parafibromin, which lose their capability to bind to Paf1 complex components (Rozenblatt-Rosen et al, 2005;Yart et al, 2005). As the missense mutation, K34Q, gives rise to a stable gene product, it is tempting to speculate that both, K34Q and L64P, represent a specific class of mutants that share a common molecular defect.…”
Section: Discussionmentioning
confidence: 99%